Fungsi Pembentukan Peraturan Daerah oleh Dewan Perwakilan Rakyat Daerah - Junimart Girsang; Mashudi Kurniawan (Journal of Law and Policy Transformation, 2017)
Legislation in Indonesia continues to experience growth, including regional governance. Previously, laws relating to local government, namely Law No. 22 of 1999 and Law No. 32 of 2004 recognize the Head of Regency/City as a local executive and the Regional Representatives Council (Parliament) as a legislative that have legislative, supervisory and and budgetary functions. Later under Law No. 23 of 2014 on Regional Government, the legislative function is altered by the function of formulating local regulations. This change is significant to be analyzed by using a normative research method to examine the position of local regulation, the function of regional regulation making and working relationships between the Head of Regioncy/City and Regional Parliament in the process of formulating local regulations. === Peraturan perundang-undangan di Indonesia senantiasa mengalami perkembangan termasuk dalam hal penyelenggaraan pemerintahan daerah. Sebelumnya Undang-Undang tentang Pemerintahan Daerah Nomor 22 Tahun 1999 dan Undang-Undang Nomor 32 Tahun 2004 mengenal Kepala Daerah dan perangkat daerah sebagai eksekutif dan Dewan Perwakilan Rakyat Daerah sebagai legislatif yang memiliki fungsi legislasi, fungsi pengawasan dan fungsi anggaran. Dalam perkembangannya, Undang -Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah fungsi legislasi diubah menjadi fungsi pembentukan peraturan daerah. Perubahan tersebut perlu dianalisis secara yuridis dengan menggunakan metodelogi penelitian yuridis normatif yang menganalisis kedudukan peraturan daerah, fungsi pembentukan peraturan daerah dalam penyelenggaraan pemerintahan dan hubungan kerja Kepala Daerah dengan DPRD dalam proses pembentukan peraturan daerah.